Digital (r)evolution : strategies to accelerate business transformation - Aguiar, Yuri B (John Wiley & Sons, Inc., 2020)
"Everyone in the business community agrees that digital transformation is essential, but almost nobody can define what digital transformation means to the modern enterprise. This book fills the knowledge gap, explaining why digital transformation is necessary and presenting clear action steps for executing a successful digital transformation strategy. The book includes detailed first-hand stories and examples of transformation strategies, explaining in clear language why some strategies succeed and others fail. SOCIAL MEDIA: LinkedIn (500+ connections) AUTHOR PLATFORM: Author speaks on a regular basis globally and will be leveraging his connection with HMG Strategy (a group that has access to 300,000 technology executives) PUBLICIST: Author will be hiring a publicist"--